ANALISIS PENGARUH WEBSITEDESIGN, RELIABILITY, CUSTOMER SERVICE, DAN TRUST TERHADAP ONLINE SHOPPING PADA TOKO GRAMEDIA ONLINE - KHO, JAN (Kajian Ilmiah Mahasiswa Manajemen, 2012)
The purpose of this study is to examine the effect of independent variable which are website design, reliability, customer service, and trust against dependent variable online shopping on online shop gramedia. This gramedia store is one the biggest store in Indonesia and one of them is located in Surabaya. Its provide a variety of education books, magazine etc. analytical techniques used in this study were multiple liniear regression analysis. The result showed that website design, reliability, customer service, and trust have a positive influence on online shopping that happens on online store gramedia.